Eating habits of children and adolescents and repercussions during the Covid-19 pandemic (Research, Society and Development, 2022)
Objective: this work aims to verify publications on the eating habits of children in the literature during the Covid-19 pandemic. Methodology: it consists of an integrative literature review study, of a qualitative and exploratory nature, with a theoretical approach. In which the two-year time frame was used for the selection of original articles in Portuguese and English. Results: the impacts caused by the Covid-19 pandemic on the eating habits of children and adolescents imply greater negative than positive changes in health. Conclusion: the cataloged studies denoted an increase in body weight, increased consumption of energy-dense foods, reduced physical activity, longer use of cell phones, computers, televisions and tablets, triggering a worsening in posture and poor sleep quality of children and adolescents during social isolation. We consider it essential to carry out new intervention studies to combat the problem of excess weight and obesity, considering that the consequences of a short period of time of the pandemic are not the causes of these health problems, recurring disorders before the pandemic.